Attitudes Toward Inclusive Education: Predictors Among Hungarian Teachers in Transylvania - GÁLFI, Bernadette; ZSOLDOS-MARCHIȘ, Iuliana (Studia Universitatis Babeș-Bolyai Psychologia-Paedagogia, 2026)
The aim of this study is to highlight the demographic, disability-specific, pedagogical, and psychological factors that may predict Hungarian teachers’ attitudes toward inclusive education in Transylvania. The study involved N = 233 teachers who completed a self-report demographic questionnaire and a set of instruments comprising the Sentiments, Attitudes, and Concerns about Inclusive Education Scale, the Attitudes and Perspectives Toward Persons with Disabilities Scale, the Special Education Preparedness Scale, and the Tolerance and Acceptance of Difference Scale. Hierarchical regression analyses indicated that positive attitudes toward inclusion were most strongly predicted by special education preparedness and direct experiences with students with special educational needs (SEN), both within and outside of school contexts. Negative emotions toward SEN individuals emerged as the most significant inhibitory factor. Neither years of professional experience nor the type of teaching environment were significant predictors. The results support the Knowledge-Attitude-Behavior theoretical framework, suggesting that knowledge and experience jointly shape attitudes, which in turn influence behavior, in this case pedagogical practice. The findings underscore the importance of experiential, empathy-building teacher education that integrates special education knowledge to foster inclusive orientations. ABSTRAKT. Ziel dieser Studie ist es, demografische, behindertenspezifische, pädagogische und psychologische Faktoren aufzuzeigen, die die Einstellungen ungarischer Lehrkräfte in Siebenbürgen gegenüber inklusiver Bildung vorhersagen können. An der Studie nahmen N = 233 Lehrkräfte teil, die einen demografischen Selbstbericht sowie einen Instrumentensatz bearbeiteten, bestehend aus der Sentiments, Attitudes, and Concerns about Inclusive Education Scale, der Attitudes and Perspectives Toward Persons with Disabilities Scale, der Special Education Preparedness Scale und der Tolerance and Acceptance of Difference Scale. Hierarchische Regressionsanalysen zeigten, dass positive Einstellungen gegenüber Inklusion am stärksten durch die sonderpädagogische Vorbereitung und direkte Erfahrungen mit Schülerinnen und Schülern mit sonderpädagogischem Förderbedarf (Special Education Need, SEN) sowohl innerhalb als auch außerhalb der Schule vorhergesagt wurden. Negative Emotionen gegenüber SEN-Personen stellten den bedeutendsten hemmenden Faktor dar. Weder die Dauer der Berufserfahrung noch die Art der Unterrichtsumgebung erwiesen sich als signifikante Prädiktoren. Die Ergebnisse stützen den theoretischen Rahmen des Knowledge-Attitude-Behavior-Modells, wonach Wissen und Erfahrung gemeinsam Einstellungen formen, die wiederum das Verhalten, in diesem Fall die pädagogische Praxis, beeinflussen. Die Befunde betonen die Bedeutung erfahrungsorientierter, empathiefördernder Lehrkräfteausbildung, die sonderpädagogisches Wissen integriert, um inklusive Haltungen zu fördern. Schlüsselwörter: inclusive Pädagogik, Einstellungen, sonderpädagogischer Förderbedarf, sonderpädagogische Vorbereitung, Toleranz, Knowledge-Attitude-Behavior (KAB)-Modell